DEVELOPMENT OF SEX EDUCATION BOOKS FOR ELEMENTARY SCHOOL STUDENTS - Mimin Ninawati (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study was to develop sex education books that have valid, feasible, and effective criteria used to convey sex education. The book development model uses the Borg and Gall development model, namely information gathering, planning, development of initial product drafts, expert testing, small scale testing, field testing, and dissemination and implementation. Based on the test of media, material, and psychologist experts, it was concluded that the sex education book fulfilled valid criteria. Then in the small-scale test it was concluded that the sex education book could be accepted and changed the way students view sex education. Sex education books can be used in field- scale tests with more populations.